Preoperative echocardiographic parameters predict primary graft dysfunction following pediatric lung transplantation. (19th October 2020) - Himebauch, Adam S.; Wong, Wai; Wang, Yan; McGowan, Francis X.; Berg, Robert A.; Mascio, Christopher E.; Kilbaugh, Todd J.; Lin, Kimberly Y.; Goldfarb, Samuel B.; Kawut, Steven M.; Mercer‐Rosa, Laura; Yehya, Nadir
Abstract: The importance of preoperative cardiac function in pediatric lung transplantation is unknown. We hypothesized that worse preoperative right ventricular (RV) systolic and worse left ventricular (LV) diastolic function would be associated with a higher risk of primary graft dysfunction grade 3 (PGD 3) between 48 and 72 hours. We performed a single center, retrospective pilot study of children (<18 years) who had echocardiograms <1 year prior to lung transplantation between 2006 and 2019. Conventional and strain echocardiography parameters were measured, and PGD was graded. Area under the receiver operating characteristic (AUROC) curves and logistic regression were performed. Forty‐one patients were included; 14 (34%) developed PGD 3 and were more likely to have pulmonary hypertension (PH) as the indication for transplant ( P = .005). PGD 3 patients had worse RV global longitudinal strain ( P = .01), RV free wall strain (FWS) ( P = .003), RV fractional area change ( P = .005), E/e' ( P = .01) and lateral e' velocity ( P = .004) but not tricuspid annular plane systolic excursion ( P = .61). RV FWS (AUROC 0.79, 95% CI 0.62‐0.95) and lateral e' velocity (AUROC 0.87, 95% CI 0.68‐1.00) best discriminated PGD 3 development and showed the strongest association with PGD 3 (RV FWS OR 3.87 [95% CI 1.59‐9.43], P = .003; lateral e' velocity OR 0.10 [95% CI 0.01‐0.70], P = .02). These associations remained when separately adjusting for age, weight, primary PH diagnosis, ischemic time, and bypass time. In this pilot study, worse preoperative RV systolic and worse LV diastolic function were associated with PGD 3 and may be modifiable recipient risk factors in pediatric lung transplantation.